PENGARUH KREDIBILITAS PENDAKWAH DAN TERPAAN MEDIA SOSIAL DAKWAH TERHADAP TINGKAT RELIGIUSITAS REMAJA DI KOTA PEKANBARU - Nuzila Fitria; Anuar Rasyid; Zulkarnain Zulkarnain (Medium: Jurnal Ilmiah Fakultas Ilmu Komunikasi, 2021)
The role of religiosity in suppressing crime and on changing adolescent behavior has been studied widely; however, studies on the influence of the preacher’s credibility and social media exposure are still limited. This study aims to examine the influence of the preacher’s credibility with the media exposure on the religiosity of adolescents in Pekanbaru. Even though similar studies have been done by other authors, this research has a different view and analysis. This research is based on cognitive theory as the Grand Theory and S-O-R Theory as the Middle Theory which explains the relationship between these three variables. Meanwhile, the Source Credibility Theory and the Hypodermic Needle Theory are applied theories that can explain the effect of the independent variables. This research was conducted on 96 moslem adolescent respondents in Pekanbaru who met certain criteria. Data were analyzed using a quantitative approach, using multiple linear regression analysis, in which each variable was also described descriptively. The results of this study prove that the credibility of preachers and social media exposure simultaneously have a significant influence on adolescent religiosity in Pekanbaru with a significance value of 0.00 (<0.05) the correlation coefficient result is 0,569. The variables of the preacher’s credibility and the preaching social media exposure contributed 32% in influencing the teenage religiosity variable. However, if it is examined partially, only the social media exposure variable of religious preaching has a direct effect on religiosity.